Respon Gereja Terhadap Isu Etnisitas dan Agama dalam masyarakat Multikultural - Julliard, Devrinho; Lattu, Izak; Tampake, Tony (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
Rejection of leaders of different religions, ethnicities and so on is the main in the 2017 DKI Jakarta Governor Election, especially narratives of indigenous and non-indigenous sentiment. The church should take a role in responding to this problem. The research method that the author will use in this paper is the qualitative method of descriptive analysis. The author will also analyze the problem of why ethnicity is used as a political tool and will explore how the issue of ethnicity occurs in Indonesia and the functional role of the church in seeing this. This research uses theories about identity politics, religion in the public sphere by Habermas, Talcott Parsons' structural functionalism and Hendropuspito's religious functionalism. In a social society, of course religion as a social institution has a role and function in responding to situations that occur around it. The church does not mean being silent but has a prophetic voice to respond to this. This shows an important transformative role, namely instilling the value of renewing understanding in church members and the surrounding community about the importance of living together in a multiethnic society.